2013
DOI: 10.1103/physrevb.87.085121
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxy-distorted spin-orbit Mott insulator in Sr2IrO4thin films

Abstract: High quality epitaxial thin films of J eff =1/2 Mott insulator Sr 2 IrO 4 with increasing inplane tensile strain have been grown on top of SrTiO 3 (001) substrates. Increasing the inplane tensile strain up to ~0.3% was observed to drop the c/a tetragonality by 1.2 %. X-ray absorption spectroscopy detected a strong reduction of the linear dichroism upon increasing in-plane tensile strain towards a reduced anisotropy in the local electronic structure. While the most relaxed thin film shows a consistent dependenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…In this review, we focused on one material system, the square lattice iridate Sr 2 IrO 4 , for which the central issue has been whether it would display HTSC like cuprates. Even staying within this somewhat narrow scope, limited space did not allow us to touch upon different approaches to metallize Sr 2 IrO 4 through epitaxial thin films [137,138], high pressure [139,140], gating [141,142], and other chemical routes [143]. So far, the most promising results have been obtained from in situ doping used in combination with ARPES and STS, but the extreme surface sensitivity of these methods is a serious impediment to further scientific progress.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we focused on one material system, the square lattice iridate Sr 2 IrO 4 , for which the central issue has been whether it would display HTSC like cuprates. Even staying within this somewhat narrow scope, limited space did not allow us to touch upon different approaches to metallize Sr 2 IrO 4 through epitaxial thin films [137,138], high pressure [139,140], gating [141,142], and other chemical routes [143]. So far, the most promising results have been obtained from in situ doping used in combination with ARPES and STS, but the extreme surface sensitivity of these methods is a serious impediment to further scientific progress.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies of SIO under epitaxial strain condition, both from theory and experiments. Samples of SIO have been grown epitaxially on a number of substrates such as SrTiO 3 , LaAlO 3 , GdScO 3 , etc [11][12][13]. Resistivity and optical absorption measurements on these structures have shown that the Mott-Hubbard gap is preserved under epitaxial strain, but its magnitude can be tuned by varying the strain.…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal oxides with partially filled d-electron states exhibit exceptionally rich electronic and magnetic phase diagrams. [1][2][3] Strong Coulomb interactions in narrow 3d-bands can lead to Mott insulators ground states. Moving down into 5d transition metal ions, the spatial extent of the orbitals increases, resulting in a stronger 5d-O:2p overlap.…”
Section: Introductionmentioning
confidence: 99%
“…Coulomb interactions or additional structural distortions introduce further splitting in that narrow J eff =1/2 band, opening up a charge gap, which can be manipulated by epitaxial strain. [4][5][6][7][8][9][10][11][12][13] The Ruddlesden-Popper (RP) series of strontium iridates, Sr n+1 Ir n O 3n+1 , features a localized-to-itinerant crossover from that insulating ground state of Sr 2 IrO 4 (with a two dimensional IrO 6 corner-sharing octahedral network characteristic of n = 1) to a correlated metallic state in the three dimensional perovskite SrIrO 3 (n = ∞). 14 This suggests the possibility of fine-tuning the charge gap across Sr n+1 Ir n O 3n+1 by growing high quality epitaxially strained thin films.…”
Section: Introductionmentioning
confidence: 99%